Colloidal characteristics of aluminum hyd roxide dispersions depending on coagulant composition and pH regulator dosing method - Anushko, Ruslan A.; Zyhmant, Alesia V.; Savitskaya, Tatsiana A.; Tsyhankova, Nadzeia G.; Hrynshpan, Dzmitry D. (Journal of the Belarusian State University. Chemistry, 2019)
The effect of aluminum coagulants composition and pH regulator dosing method on colloidal characteristics of aluminum hydroxide dispersions (diameter, particle size distribution, density and sedimentation rate of aggregates) was investigated by using of laser diffraction method. Highly basic polyaluminum chloride «Brilliant-50» was established to form aggregates of larger size and lower density than aluminum sulfate. Size and density of the aluminum sulfate aggregates were found to be a function of the pH dosing method (multi- or single-stage dosing). This effect became more evident when powdered coagulant was used as compared to its solution. According to computational study results hydration of aluminum polynuclear hydroxocomplexes increased with their molecular mass increasing, and consequently density of coagulation aggregates formed by them was suggested to decrease.
Keywords: dispersions; coagulants; aluminum sulfate; polyaluminum chloride; sedimentation rate; pH regulator; aluminum hydroxide